Pengelolaan Pembelajaran Dalam Penanaman Nilai-Nilai Karakter Di Madrasah Ibtidaiyah Negeri Gabugan Kabupaten Sragen - Setyomukti, Eni; , Prof.Dr. Markamah, M. Hum; , Dr. Darsinah, M. Si (2016)
Eni Setyomukti, Q 100120103. In the Learning Management Investment Values Character in State Government Elementary School Gabugan Sragen. Thesis. Surakarta Muhammadiyah University Graduate Program. 2016. Planting the character value is an effort to realize the hopes of the nation through education. In the last decade, education is only the aspects of academic than emotional and spiritual aspects. The rise of national and international Olympiad in math and science is one of the proofs. This research was conducted in MIN Gabugan, arguing that the public perception in charge of religious instruction MIN more so will unlock the value of religious character as the basis for the establishment of good morals. The purpose of this study was to describe the planning, implementation, and evaluation of learning in the cultivation of character values in MIN Gabugan. This research is a qualitative descriptive study single case study approach and descriptive methods. Data of this study include data on planning, implementation, and evaluation of learning the characters. The data source of this research is the document/ records and informants. Interviewees of research is the principal, teachers, students and parents/ guardians. Data collection techniques are observation, study of documents, and interviews. Analysis of data using an interactive model. This study has three outcomes. 1. Planning learning in teaching planned to develop syllabi and lesson plans that already exist in accordance with the vision and mission of the school. Preparing the materials, methods, and learning media to support teaching and learning process. Planning in Non-teaching schools meet with the committee to discuss character education program. Then socializing. 2. Implementation of learning the character values in teaching and learning activities carried out by integrating the value of the character during the learning process based on the circumstances and the selection of the subject matter by the teacher. Planting seedlings Non-teaching character values in MIN Gabugan do with acculturation and habituation program, extracurricular, and counseling. 3. Evaluation of learning in the planting of the character values in MIN Gabugan done with non-academic assessment using observation and journals. Keywords: Management, Learning, Character